Sandwich structure ultralight prepreg and preparation and forming process thereof
By adopting the molding process of ultra-light prepreg in sandwich structure, the curing of thermal self-expanding layers and continuous fibers, the thin-walled products are integrated to solve the problems of complex processes and unavailable in the existing technology, and the high efficiency is achieved. Low cost production and improves the mechanical properties and consistency of the products.
Patent Information
- Application Number
- CN202411538633.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The existing sandwich structure composite molding process has the problem of complex process, unavailable special-shaped structures or low yield. Especially in the molding process of thin-walled special-shaped parts, it is difficult to achieve efficient and low-cost production.
Using a sandwich structure ultralight prepreg, including the first fiber reinforcement layer, the thermal self-expanding layer and the second fiber reinforcement layer, the thin-walled product is formed integrally through free foaming of the thermal self-expanding layer and the curing of continuous fibers, and the process is simplified. Process and improve productivity.
The efficient molding of thin-walled special-shaped parts is achieved, and the production cost is reduced, the density can be as low as 0.5g/cm3-1.2g/cm3, the weight is reduced by 30%, and the mechanical properties and consistency of the products are improved.
Smart Images

Figure CN119408243A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to composite material technology and its molding application field, and in particular to an ultra-light prepreg material with a sandwich structure and its preparation and molding process. Background Art
[0002] With the rapid development of material technology and molding technology and the increasing requirements for material performance, lightweight and high-strength carbon fiber reinforced resin-based sandwich structure composite materials have expanded their applications in various fields. The density of ordinary carbon fiber reinforced resin-based composite materials is 1.5-1.8g / cm 3 , it is difficult to meet the requirements of consumer electronics, aerospace and other fields that have more stringent requirements on weight control. It is necessary to further carry out sandwich structure design in order to achieve the ultimate lightness while meeting the requirements of high strength. Currently, the widely used method is to use foam or paper honeycomb as the sandwich layer and fiber fabric as the reinforcement material to obtain a lightweight and high-strength composite material.
[0003] The main sandwich structure composite material forming processes at present are compression molding and autoclave. Both methods first process and form a foam preform, then need to carve, cut, grind or punch according to the designed size or shape, and then lay the prepreg on the surface of the core mold to form it. Even a rolling process is required to improve the bonding strength between the sandwich layer and the prepreg. In other words, the foam preform is obtained by machining and carving, rather than by mold forming, and there is a problem of non-conformity, especially in the molding process of thin-walled and special-shaped sandwich structure composite materials, which is easy to cause local dry yarn or foam and skin delamination. In addition, the compression molding method will apply a large external pressure in the early stage. If it is not well controlled, it will cause the resin to overflow the mold and cause the product to lack glue; although the autoclave can achieve segmented pressurization and solve this problem, the high cost of the autoclave limits its scope of use. Whether it is the compression molding method or the autoclave method, there are problems such as complex process, the inability to realize special-shaped structures or low yield, and many steps involved in manual operation and long time consumption.
[0004] KR101928236B1 and CN108638530B disclose a method for manufacturing a three-layer lightweight sandwich structure based on thermoplastic resin using a co-extrusion process and a lightweight sandwich structure manufactured by the method, which simplifies the complex molding process into a co-extrusion step. Alternatively, unidirectional fiber bundles are directly used as the skin shell, foam is used as the core material, and an injection molding stretch-compression molding process is used to continuously produce sandwich core structure composite materials in one step. However, only equal-thickness flat plates can be manufactured, and it is difficult to process special-shaped parts such as unequal-thickness thin plates.
[0005] CN200810054400.5 relates to a composite material with a foam core integral structure and a preparation method thereof. The composite material comprises an upper layer, a lower layer and a foam core layer, the foam core layer and the upper and lower layers are sewn together as a whole by sutures, and are once-injected by a resin transfer molding process. The outer surfaces of the upper and lower layers are flat and smooth, the composite material has good integrity, long service life, precise shape, structure and size, and excellent mechanical properties. When it comes to special-shaped parts, there are also complex steps such as cutting and carving of the foam core layer, and thin plate parts cannot be molded.
[0006] Therefore, breaking through the limitations of special-shaped parts, simplifying steps, improving production efficiency, and reducing labor costs are pain points that companies using this structure urgently need to solve.
[0007] Patent CN101010188B discloses a sandwich structure that can be used to form a thin-walled molded body with a thickness of 0.1mm-1.5mm and a complex shape. Its polyolefin thermoplastic resin foam core material is a core material that satisfies both lightness and thin-wall properties and has excellent practicality. It achieves the purpose of batch-molding thin-walled special-shaped parts in one piece through the high-temperature compressibility of the foamed thermoplastic resin; however, its core material preparation process involves complex and energy-intensive processes such as self-heating cladding, vibration cladding, ultrasonic cladding, laser cladding, insert molding, and out-sert molding, while the surface prepreg is still a traditional hot-melt coating process, which involves a large investment in equipment; structurally, a layer of hot-melt bonding structure is required between the core material and the surface prepreg to ensure the bonding strength, which is a big challenge to cost and process as a whole; so although it is better than traditional prepreg foam sandwich materials such as PMI, polyurethane, and honeycomb core in thin-walled special-shaped parts, it still cannot be used on a large scale.
[0008] In order to solve the above-mentioned industry problems, after years of experiments, the present invention application is proposed. Summary of the invention
[0009] The present invention aims to overcome the defects of existing commercial prepregs and provide an ultra-light prepreg with a sandwich structure. Prepreg is a common dry fiber reinforcement, which is made by impregnating continuous fibers or fabrics with a resin matrix under strictly controlled conditions to form a combination of resin matrix and dry fibers, such as carbon fiber or glass fiber prepreg. The existing prepreg fibers and resin are fused together, which is actually a single layer material that cannot be physically separated.
[0010] Another object of the present invention is to provide a preparation method and a molding process of the above-mentioned ultra-light prepreg, which overcomes the difficulties and limitations of the molding process of traditional conventional sandwich structures, especially thin-walled special-shaped structures. It is different from the foaming method of traditional PVC, PMI and other shaped foams that are first foamed and shaped and then formed with the skin and core. It can not only solve the molding problem of complex shapes or thin-walled special-shaped structures, but also ensure that the products have good performance and reduce production costs.
[0011] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a sandwich structure ultra-light prepreg, comprising a first fiber reinforcement layer, a thermal self-expansion layer and a second fiber reinforcement layer, the thermal self-expansion layer is located between the first fiber reinforcement layer and the second fiber reinforcement layer; the thermal self-expansion layer has a square gram weight of 100g-300g, a thickness of 0.1mm-2mm, and a free foaming ratio of 3-30 times; the first fiber reinforcement layer and the second fiber reinforcement layer are made of the same material, including a continuous phase and a reinforcing phase, wherein the reinforcing phase is 30g-150g of unidirectional continuous or woven fiber, the continuous phase is a low-temperature fast-curing system thermosetting resin glue, and the first fiber reinforcement layer and / or the second fiber reinforcement layer contain 30%-50% glue; the thermal self-expansion layer adopts a main resin having the same curing system as the continuous phase; the sandwich structure ultra-light prepreg is used to form thin-walled products with a thickness of 0.4mm-2mm.
[0012] Preferably, the continuous phase is composed of 30-70 parts by weight of thermosetting epoxy resin, 0-20 parts by weight of toughening agent, 1-15 parts of curing agent, and 0-5 parts of accelerator.
[0013] Preferably, the thermal self-expansion layer is composed of 30-70 parts by weight of thermosetting epoxy resin, 0-20 parts by weight of toughening agent, 1-15 parts of curing agent, 0-5 parts of accelerator and 1-20 parts by weight of foaming agent. The thermal self-expansion layer is the same as the main resin of the continuous phase of the fiber layer, and the curing system is the same, and the reactive groups are consistent. The two are the same resin system and the same curing system, which means that their cross-linking reactions are consistent, the curing speed is consistent, and the resin modulus and strength are consistent, and the only difference is whether there is foaming property. There is no interface between the thermal self-expansion layer of the cured product and the first fiber reinforcement layer or the second fiber reinforcement layer, and the only difference is the density.
[0014] Preferably, the reinforcing phase is any one of carbon fiber, glass fiber, aramid unidirectional continuous fiber or fabric, or a combination of several fabrics.
[0015] Preferably, the reinforcing phase has a gram weight of 30 g / m 2 -200g / m 2 , thickness 0.1mm-0.25mm.
[0016] The present invention also provides a method for preparing an ultra-light prepreg with a sandwich structure, comprising the following steps:
[0017] First, the resin rubber compound is prepared: 30-70 parts by weight of thermosetting epoxy resin, 0-20 parts by weight of toughening agent, 1-15 parts of curing agent, and 0-5 parts of accelerator are mixed evenly, and the rubber compound A is formed after vacuum degassing to be used as the continuous phase; 30-70 parts by weight of thermosetting epoxy resin, 0-20 parts by weight of toughening agent, 1-15 parts of curing agent, 0-5 parts of accelerator and 1-20 parts by weight of foaming agent are mixed evenly, and the rubber compound B is formed after vacuum degassing;
[0018] Second, preparation of the fiber reinforcement layer: according to the designed fiber surface density and rubber weight, the rubber A is coated and the thickness is determined on a fabric machine using release paper as a carrier by hot melt coating, and then pre-impregnated with continuous fiber woven cloth or unidirectional yarn on a dipping machine to form the first fiber reinforcement layer and the second fiber reinforcement layer;
[0019] Third, thermal self-expanding layer coating: using the first fiber reinforced layer prepared in the second step as a carrier, coating the rubber material B as the thermal self-expanding layer according to the designed gram weight; using a compounding machine to compound the second fiber reinforced layer on top of the thermal self-expanding layer to obtain the ultra-light prepreg.
[0020] Preferably, the resin compound is prepared by using a planetary mixer for three times for more than 10 minutes, and the compound is degassed under a vacuum pressure of more than -0.095 MPa.
[0021] Preferably, the temperature of the resin compound is controlled at 38°C-45°C during preparation in the first step.
[0022] Preferably, the temperature during the second or third coating step is controlled at 50°C-80°C.
[0023] Preferably, in the second step, the dipping temperature is controlled to be 90° C.-100° C., and the dipping pressure is 0.6 MPa-0.8 MPa.
[0024] Preferably, in the first step, the thermosetting epoxy resin is a low-temperature fast-curing epoxy resin, and the weight of the adhesive A is 20g-150g.
[0025] Preferably, the thermal self-expanding layer of the ultralight prepreg has a square gram weight of 100 g to 300 g, a thickness of 0.1 mm to 2 mm, and a free foaming ratio of 3 to 30 times.
[0026] The present invention also provides a curing molding process for an ultra-light prepreg with a sandwich structure, comprising the following steps:
[0027] First, the ultra-light prepreg is cut according to the plane size, and after cutting, it is directly placed into the preheated mold cavity so that it fits tightly with the lower wall of the mold;
[0028] Second, the mold is closed, the pressure is increased, and the pressure is maintained and heated for molding; the molding pressure is controlled at 5MPa-30MPa, and the pressure increase rate is controlled at 0.1MPa / s-10MPa / s; the molding time is 3min-10min.
[0029] Third, a continuous mold warm-in-hot-out process allows demoulding without cooling, and the product can be taken out to obtain a composite material with a sandwich structure; wherein the continuous mold temperature is 110°C-150°C.
[0030] Beneficial effects: The one-piece forming process of the present invention is not only suitable for plates and bars but also suitable for forming special-shaped products, especially thin-walled products of unequal thickness.
[0031] 1. The sandwich structure ultra-light prepreg obtained by the process of the present invention can have a density as low as 0.5g / cm after curing. 3 -1.2g / cm 3 , the weight is reduced by 30% compared with the prepreg of non-foamed sandwich structure under the same specifications.
[0032] 2. The thermal self-expanding layer of the present invention expands freely when heated and foams to fill the mold cavity, and then solidifies and shapes together with the continuous fiber woven cloth or unidirectional yarn. There is no need to carve or cut the foam. The shape and thickness have high freedom within the recommended product ratio range. The thickness of the finished product can be as low as 0.4mm as required. It is one-piece molded and is friendly to special-shaped structures.
[0033] 3. The preparation process of the ultra-light prepreg of the present invention is consistent with the coating process, without other equipment, and the process is not significantly different from the conventional prepreg coating. The process is mature and stable, and the product consistency is good.
[0034] 4. The ultra-light prepreg of the present invention is suitable for a 110°C-150°C hot-in, hot-out, low-temperature fast-curing process, can be demoulded in 3min-10min, has extremely high production efficiency under continuous mold temperature, and is suitable for large-scale production lines such as 3C electronics. After hot demoulding, the warpage is as low as 0.75%, the volume shrinkage is less than 0.2%, and the dimensional stability is good.
[0035] 5. The molding process is extremely simple. The steps of carving / cutting, grinding / drilling, manual folding, molding, cooling and demolding are reduced to just cutting and molding, which saves the labor cost of multiple steps and improves production efficiency.
[0036] 6. High yield rate. It not only reduces the errors and defects caused by manual operation, but also the internal pressure caused by the expansion ratio of the material itself during the molding process, combined with the mold cavity, will greatly help the molding appearance of the carbon fiber skin, reduce defects such as lack of glue, and reduce surface porosity.
[0037] 7. The foamed core layer formed by the thermal self-expansion layer of the present invention has the same resin cross-linking reaction group as the substrate, and cures synchronously. It has better bonding with the skin than thermoplastic resin foams such as PVC and polyolefins. It does not require an additional adhesive structural layer or the use of adhesives, nor does it require rolling. The bonding peel strength between the surface substrate and the foamed core layer can reach more than 3MPa.
[0038] 8. Like conventional carbon fiber prepregs, the ultralight prepreg of the present invention also has various weaving patterns and weights. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Schematic diagram of the state before and after heating and forming of Example 1 of the present invention;
[0040] Figure 2 Schematic diagram of the state before and after heating and forming of Example 2 of the present invention;
[0041] Figure 3 It is a cross-sectional view of the finished thin plate of the present invention, wherein the thermal self-expansion layer is located between the first fiber-reinforced layer and the second fiber-reinforced layer, forming an integral sandwich structure.
[0042] Explanation of reference numerals: 1. first fiber-reinforced layer; 2. thermal self-expansion layer; 3. second fiber-reinforced layer. DETAILED DESCRIPTION
[0043] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. It should be clear that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] The "first\second" mentioned in the embodiments is only to distinguish similar objects, and does not represent a specific order for the objects. It is understandable that the "first\second" can be interchanged with the specific order or sequence where permitted. It should be understood that the objects distinguished by "first\second" can be interchanged where appropriate, so that the embodiments described herein can be implemented in an order other than those illustrated or described herein.
[0045] The test materials and equipment used in the present invention are all common commercial products and can be purchased on the market. In order to solve the problem of difficulties and limitations in the molding process of conventional carbon fiber composite foam sandwich structures. The patent of the present invention provides an ultra-light prepreg material for a sandwich structure and a preparation and one-piece molding process. It is different from the foaming method of the traditional PVC, PMI and other shaped foams that are first foamed and shaped and then sandwiched with the prepreg. It can not only solve the molding problem of complex shapes or thin-walled special shapes, but also improve the delamination phenomenon of the surface layer and the core layer of the sandwich structure due to the inconsistency of the resin system, ensuring that the product has good performance; it can be directly cut into the mold for molding, reducing the process and reducing the production cost.
[0046] A sandwich structure ultra-light prepreg, comprising a first fiber reinforcement layer 1, a thermal self-expanding layer 2 and a second fiber reinforcement layer 3, wherein the thermal self-expanding layer 2 is located between the first fiber reinforcement layer 1 and the second fiber reinforcement layer 3; the thermal self-expanding layer 2 has a square gram weight of 100g-300g, a thickness of 0.1mm-2mm, and a free foaming ratio of 3-30 times; the first fiber reinforcement layer 1 and the second fiber reinforcement layer 3 are made of the same material, including a continuous phase and a reinforcing phase, wherein the reinforcing phase is 30g-150g of unidirectional continuous or woven fiber, the continuous phase is a low-temperature fast-curing system thermosetting resin glue, and the first fiber reinforcement layer 1 and / or the second fiber reinforcement layer 3 contain 30%-50% glue; the sandwich structure ultra-light prepreg is used for molding thin-walled products with a thickness of 0.4mm-2mm.
[0047] Preferably, the continuous phase is composed of 30-70 parts by weight of thermosetting epoxy resin, 0-20 parts by weight of toughening agent, 1-15 parts of curing agent, and 0-5 parts of accelerator.
[0048] Preferably, the thermal self-expansion layer 2 is composed of 30-70 parts by weight of thermosetting epoxy resin, 0-20 parts by weight of toughening agent, 1-15 parts of curing agent, 0-5 parts of accelerator and 1-20 parts by weight of foaming agent. The thermal self-expansion layer 2 is the same as the main resin of the continuous phase, and has the same curing system and the same reactive groups. That is to say, the same resin system, the same curing system represents the same cross-linking group, the same curing speed, the same resin modulus strength, and the only difference is whether there is foaming. There is no interface between the cured product thermal self-expansion layer 2 and the first fiber reinforcement layer 1 or the second fiber reinforcement layer 3, and the only difference is the density.
[0049] Preferably, the reinforcing phase is any one of carbon fiber, glass fiber, aramid unidirectional continuous fiber or fabric, or a combination of several fabrics.
[0050] Preferably, the reinforcing phase has a gram weight of 30 g / m 2 -200g / m 2 , thickness 0.1mm-0.25mm.
[0051] The present invention also provides a method for preparing an ultra-light prepreg with a sandwich structure, comprising the following steps:
[0052] First, the resin rubber compound is prepared: 30-70 parts by weight of thermosetting epoxy resin, 0-20 parts by weight of toughening agent, 1-15 parts of curing agent, and 0-5 parts of accelerator are added to a planetary mixer and mixed evenly. After three vacuum degassings, rubber compound A is formed as the continuous phase; 30-70 parts by weight of thermosetting epoxy resin, 0-20 parts by weight of toughening agent, 1-15 parts of curing agent, 0-5 parts of accelerator and 1-20 parts by weight of foaming agent are added to a planetary mixer and mixed evenly. After three vacuum degassings, rubber compound B is formed. The vacuum degassing pressure is above -0.095MPa. The temperature is controlled at 38℃-45℃ during the preparation of the resin rubber compound. If the temperature is too low, the viscosity of the rubber compound is large and the degassing effect is poor. If the temperature is too high, there is a risk of explosion.
[0053] Among them, the foaming agent can be a chemical foaming agent or a physical foaming agent, such as azodicarbonamide, azobisisobutyl cyanide or expanded microspheres, etc. It should be noted that the initial foaming temperature and time point of the foaming agent must be compatible with the curing system. The toughening agent is a rubber toughening agent or a thermoplastic resin modified epoxy, etc. The curing agent is a latent curing agent, such as a modified aliphatic, aromatic amine, dicyandiamide, anhydride or microcapsule curing agent, and the accelerator is a tertiary amine, a modified amine, an organic urea, an organic guanidine, etc.
[0054] Second, preparation of the fiber reinforcement layer: according to the designed fiber surface density and grammage of the adhesive, the adhesive A is coated and thickened on the cloth machine using release paper as the carrier by hot melt coating, and then pre-impregnated with continuous fiber woven cloth or unidirectional yarn on the dipping machine to form the first fiber reinforcement layer 1 and the second fiber reinforcement layer 3. The temperature is controlled at 50℃-80℃ during coating; if the temperature is too low, the viscosity of the resin is high, and the coating appearance is prone to poor; if the temperature is too high, the resin fluidity is too high, which can easily cause uneven coating thickness control. The dipping temperature is controlled at 90℃-100℃, and the dipping pressure is 0.6-0.8MPa. If the dipping temperature is too low, the viscosity of the resin is high and it is difficult to penetrate the gaps between the fibers; if the dipping temperature is too high, it may reach the starting point of the reaction system, and there is a risk of resin aging.
[0055] Third, coating of the thermal self-expansion layer 2: using the first fiber reinforcement layer 1 prepared in the second step as a carrier, coating the rubber material B as the thermal self-expansion layer 2 according to the designed gram weight; using a compounding machine to compound the second fiber reinforcement layer 3 on the thermal self-expansion layer 2 to obtain the ultra-light prepreg. The temperature during coating is controlled at 50°C-80°C. The square gram weight of the thermal self-expansion layer 2 is 100g-300g, the thickness is 0.1mm-2mm, and the free foaming ratio is 3-30 times.
[0056] On the other hand, since the fiber is impregnated with the resin containing the curing agent and the thermal self-expanding layer 2 in advance, if one wants to use the ultra-light prepreg of the present invention to make a product, one only needs to directly attach the ultra-light prepreg to the mold and heat and cure it. Specifically, the following steps are included:
[0057] First, cut the above-mentioned ultra-light prepreg according to the plane size, and directly put the cut plane ultra-light prepreg into the preheated mold cavity (the mold can also be a special-shaped surface with uneven thickness) so that it fits tightly with the lower wall of the mold;
[0058] Second, the mold is closed, the pressure is increased, and the pressure is maintained and heated to form; after the mold is closed, the resin of the heat-expanding layer 2 is foamed and expanded to form the foamed sandwich layer of the product. During the foaming and expansion process, a pressure from the inside of the mold to the outside will be generated, and this pressure will continue to be applied to the outermost surface substrate until the foaming is completed. During the foaming process, the heat-expanding layer 2 and the thermosetting resin rubber on the fiber reinforcement layer are integrally cured to obtain the desired equal thickness or non-equal thickness sandwich structure composite material. The molding pressure is controlled at 5MPa-30MPa, and the pressure increase rate is controlled at 0.1MPa / s-10MPa / s. There are one or two pressure relief behaviors before the resin gels and then the pressure is maintained. The molding time is 3min-10min.
[0059] Third, the continuous mold temperature hot in and hot out process is adopted, and the mold can be demoulded and the product can be taken out without cooling. The mold temperature during compression molding is a continuous mold temperature of 110℃-150℃.
[0060] Example 1: Forming of products of different thicknesses
[0061] Ultra-light prepreg was prepared according to the above steps and process parameters, wherein the woven carbon fiber surface density was 100 g / m 2 The resin content (RC) of the first fiber reinforced layer 1 and the second fiber reinforced layer 3 is 43%, that is, the fiber reinforced layer density is 100 / (1-0.43)=175g / m 2 ), then the upper and lower layers total 175*2=350g / m 2 ; The weight of the thermal self-expansion layer is 150g / m 2 ; The overall ultra-light prepreg weight is 500g / m 2 , thickness is 0.3mm. The temperature of the rubber compound is controlled at 38-45℃, the coating material temperature is 70℃, and the dipping machine temperature is 100℃.
[0062] Next, cut the ultra-light prepreg equal to the length and width of the mold and lay it flat on the bottom of the mold preheated to 130℃. The mold size is: length and width are 200mm*200mm, the outer thickness is 0.9mm, and the inner thickness is 0.5mm. Close the mold and heat it. After the pressure rises to 0.3Mpa, release the pressure for 5S, increase the pressure to 5Mpa in 1min, and keep the temperature and pressure for 10min. Demolding directly without cooling is the product of unequal thickness. Figure 1 As shown, before heating and molding ( Figure 1 a) and after heating and molding ( Figure 1 b) Schematic diagram of state changes.
[0063] Once again, it is emphasized that the product of the present invention has the characteristics of curing and setting after thermal self-expansion, and the integrated structure of the carbon fiber surface layer and the core layer. It only needs to cut the plane shape and put it into the designed mold cavity for hot pressing and foaming. After demolding, it will be the required low-density carbon fiber composite material foam sheet sandwich product.
[0064] The ultralight prepreg foaming layer obtained in Example 1, i.e., the thermal self-expanding layer after heating and molding, is compared with other foams of the same density, and the mechanical properties test data are shown in Table 1. The ultralight prepreg foaming layer is superior in compression strength, tensile strength, and tensile modulus: compared with other foams and prepreg sandwich molding, its shear strength and shear modulus have obvious advantages.
[0065] Table 1. Comparison of mechanical properties of ultra-light prepreg foam layer and other commercially available foams
[0066]
[0067]
[0068] Example 2-A: Forming of products of equal thickness
[0069] The surface density of woven carbon fiber is 100g / m 2 , RC = 43%, then the square gram weight of the two fiber reinforcement layers is 175*2 = 350g / m 2 ; The weight of the thermal self-expansion layer is 150g / m 2 The other parameters are the same as those in Example 1, and the overall ultra-light prepreg weight is 500g / m 2 , the design thickness is 0.5mm.
[0070] After cutting into 21*21cm, put it into a mold of the same size and thickness of 0.5mm, and hot press it at 130℃ / 7min. After hot pressing, the sheet has no warping phenomenon, the appearance is full and flat, and the foaming layer is foamed evenly. Figure 2 As shown, before heating and molding ( Figure 2 a) and after heating and molding ( Figure 2 b) Schematic diagram of state changes.
[0071] The density of the finished sheet is about 1g / cm 3 , and its mechanical properties are shown in Table 2. The density and gram weight of the product of the present invention are much lower than those of pure carbon fiber board; compared with the process of laminating the core material with commercial prepreg (i.e., using commercial carbon fiber prepreg and the thermal self-expanding layer of the present invention as the core material, the difference in the finished product lies in the different continuous phase components in the prepreg), the product of the present invention has better bonding force from the bending and shear test data. The test was carried out with reference to the national standards GB / T 1447, GB / T 1448, and GB / T1449. In order to realize the test of the thin plate sandwich structure, the custom compression stroke was 0.3mm and the bending span was 30mm.
[0072] Table 2. Comparison of mechanical properties of finished thin plates with other forming processes
[0073] project Pure carbon fiber board Example 2-A Commercially available prepreg laminated core material Thickness(mm) 0.668 0.49 0.49 <![CDATA[Grammage (g / m 2 )]]> 963 792 792 <![CDATA[Density (g / cm 3 )]]> 1.44 0.95 0.95 Compression strength(MPa) 228.995 186.237 179.415 Compression modulus (MPa) 1154.043 1221.062 1275.958 Bending strength(MPa) 1129.769 783.137 536.142 Flexural modulus(GPa) 58.002 67.700 56.214 Tensile strength(MPa) 484.712 144.603 145.178 Tensile modulus (MPa) 1668.565 2233.354 1712.142 Fracture strain ε(%) 3.87 7.64 7.84 Sandwich shear modulus (MPa) / 3.84 3.02
[0074] Example 2-B: Braided carbon fiber surface density is 200g / m 2 , RC = 33%, two layers of surface 300 * 2 = 600g / m 2 (The surface density of the entire prepreg is 200 / (1-0.333) = 300g / m 2 ); thermal self-expansion layer is 150g / m 2 ; The overall ultra-light prepreg weight is 750g / m 2 . The design thickness is 0.66mm.
[0075] After cutting into 21*21cm, it is put into a mold of the same size and thickness of 0.66mm and hot pressed at 125℃ / 10min. After heat removal, the thin plate has no warping phenomenon, the appearance is full and flat, and the foaming layer is foamed evenly.
[0076] The density of the finished sheet is about 1.14g / cm 3 The mechanical properties data are shown in Table 3. The test was carried out with reference to the national standards GB / T1447, GB / T 1448, and GB / T 1449. In order to realize the test of thin plate sandwich structure, the custom compression stroke was 0.3 mm and the bending span was 30 mm.
[0077] Table 3. Comparison of mechanical properties of finished thin plates with other forming processes
[0078] project Pure carbon fiber board Example 2-B Commercially available prepreg laminated core material Actual thickness(mm) 0.668 0.668 0.668 <![CDATA[Density (g / cm 3 )]]> 1.44 1.14 1.14 Compression strength(MPa) 228.995 216.159 215.174 Compression modulus (MPa) 1154.043 1071.363 1048.525 Bending strength(MPa) 1129.769 922.654 721.452 Flexural modulus(GPa) 58.002 47.855 41.245 Tensile strength(MPa) 484.712 415.133 410.581 Tensile modulus (MPa) 1668.565 2083.766 1789.451 Fracture strain ε(%) 3.87 4.40 4.32 Interlaminar shear strength (MPa) / 4.12 3.21
[0079] Example 2-C: Braided carbon fiber surface density is 200g / m 2 , RC = 50%, two layers of surface 400 * 2 = 800g / m 2 ; The thermal self-expansion layer is 150g / m 2; The overall ultra-light prepreg weight is 950g / m 2 .
[0080] After cutting into 21*21cm, put it into a mold of the same size and thickness of 1mm, and hot press it at 150℃ / 5min. After hot pressing, there is no warping of the thin plate, the appearance is full and smooth, and the foaming layer is foamed evenly.
[0081] The density of the finished sheet is about 0.95g / cm 3 , and its mechanical properties data are shown in Table 4. The test was carried out with reference to the national standards GB / T1447, GB / T 1448, and GB / T 1449. In order to realize the test of thin plate sandwich structure, the custom compression stroke was 0.3mm and the bending span was 30mm.
[0082] Figure 3 It is a cross-sectional view of the finished thin plate of the present invention. The white middle layer is a thermal self-expansion layer 2, which is located between the first fiber-reinforced layer 1 and the second fiber-reinforced layer 3, forming an integrally formed sandwich structure.
[0083] Table 4. Comparison of mechanical properties of finished sheets with other forming processes
[0084] project Pure carbon fiber board Example 2-C Commercially available prepreg laminated core material Actual thickness(mm) 1.005 1.004 1.004 Density(g / cm3) 1.44 0.95 0.95 Compression strength(MPa) 230.912 189.412 175.415 Compression modulus (MPa) 1168.025 985.741 992.451 Bending strength(MPa) 1134.154 922.654 689.526 Flexural modulus(GPa) 66.125 51.612 43.452 Tensile strength(MPa) 492.512 394.215 403.156 Tensile modulus (MPa) 1895.185 1985.254 1845.125 Fracture strain ε(%) 3.51 4.08 4.15 Interlayer peel strength (MPa) / 3.69 2.77
[0085] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A sandwich structure ultra-light prepreg, characterized in that: It comprises a first fiber reinforcement layer, a thermal self-expanding layer and a second fiber reinforcement layer, wherein the thermal self-expanding layer is located between the first fiber reinforcement layer and the second fiber reinforcement layer; the first fiber reinforcement layer and the second fiber reinforcement layer are made of the same material, comprising a continuous phase and a reinforcing phase, wherein the reinforcing phase is a unidirectional continuous or woven fiber, the continuous phase is a low-temperature fast-curing system thermosetting resin glue, and the first fiber reinforcement layer and / or the second fiber reinforcement layer contain 30-50% glue; the thermal self-expanding layer adopts a main resin having the same curing system as the continuous phase; the sandwich structure ultra-light prepreg is used for molding thin-walled products with a thickness of 0.4mm-2mm.
2. The sandwich structure ultra-light prepreg according to claim 1, characterized in that: The continuous phase is composed of 30-70 parts by weight of thermosetting epoxy resin, 0-20 parts by weight of toughening agent, 1-15 parts of curing agent and 0-5 parts of accelerator.
3. The sandwich structure ultra-light prepreg according to claim 1, characterized in that: The thermal self-expanding layer is composed of 30-70 parts by weight of thermosetting epoxy resin, 0-20 parts by weight of toughening agent, 1-15 parts by weight of curing agent, 0-5 parts by weight of accelerator and 1-20 parts by weight of foaming agent.
4. The ultra-light prepreg material of sandwich structure according to claim 1, characterized in that: The thermal self-expanding layer has a square gram weight of 100g-300g, a thickness of 0.1mm-2mm, and a free foaming ratio of 3-30 times.
5. The sandwich structure ultra-light prepreg according to any one of claims 1 to 4, wherein the preparation method thereof comprises the following steps: First, the resin rubber compound is prepared: 30-70 parts by weight of thermosetting epoxy resin, 0-20 parts by weight of toughening agent, 1-15 parts of curing agent, and 0-5 parts of accelerator are mixed evenly, and the rubber compound A is formed after vacuum degassing to be used as the continuous phase; 30-70 parts by weight of thermosetting epoxy resin, 0-20 parts by weight of toughening agent, 1-15 parts of curing agent, 0-5 parts of accelerator and 1-20 parts by weight of foaming agent are mixed evenly, and the rubber compound B is formed after vacuum degassing; Second, preparation of the fiber reinforcement layer: according to the designed fiber surface density and rubber weight, the rubber A is coated and the thickness is determined on a fabric machine using release paper as a carrier by hot melt coating, and then pre-impregnated with continuous fiber woven cloth or unidirectional yarn on a dipping machine to form the first fiber reinforcement layer and the second fiber reinforcement layer; Third, thermal self-expanding layer coating: using the first fiber reinforced layer prepared in the second step as a carrier, coating the rubber material B as the thermal self-expanding layer according to the designed gram weight; using a compounding machine to compound the second fiber reinforced layer on top of the thermal self-expanding layer to obtain the ultra-light prepreg.
6. The method for preparing the sandwich structure ultra-light prepreg according to claim 5, characterized in that: When preparing the resin compound, a planetary mixer is used for three times for more than 10 minutes, and a vacuum pressure of more than -0.095 MPa is used to degas the compound.
7. The method for preparing the sandwich structure ultra-light prepreg according to claim 5, characterized in that: In the first step, the temperature of the resin compound is controlled at 38°C-45°C.
8. The method for preparing the sandwich structure ultra-light prepreg according to claim 5, characterized in that: The temperature is controlled at 50°C-80°C during the second or third step of coating.
9. The method for preparing the sandwich structure ultra-light prepreg according to claim 5, characterized in that: In the second step, the dipping temperature is controlled at 90°C-100°C, and the dipping pressure is 0.6MPa-0.8MPa.
10. The method for preparing the sandwich structure ultra-light prepreg according to claim 5, characterized in that: The thermosetting epoxy resin is a low-temperature fast-curing epoxy resin, and the weight of the adhesive A is 20g-150g.
11. The method for preparing the sandwich structure ultra-light prepreg according to claim 5, characterized in that: The thermal self-expanding layer has a square gram weight of 100g-300g, a thickness of 0.1mm-2mm, and a free foaming ratio of 3-30 times.
12. A curing molding process for a sandwich structure ultra-light prepreg according to any one of claims 1 to 11, characterized in that: The following steps are involved: First, the sandwich structure ultra-light prepreg as claimed in claims 1 to 4 is cut according to the plane size, and after cutting, it is directly placed into the preheated mold cavity so that it fits tightly with the lower wall of the mold; Second, the mold is closed, the pressure is increased, and the pressure is maintained and heated for molding; the pressure is controlled at 5MPa-30MPa, the pressure increase rate is controlled at 0.1MPa / s-10MPa / s; the molding time is 3min-10min; Third, a continuous mold warm-in and hot-out process is adopted, and the product can be demoulded and taken out without cooling; the continuous mold temperature is 110℃-150℃.
Citation Information
Patent Citations
Sandwich structure and integrated formed article using the same
CN101010188B
Foam sandwich extensional organization composite material and method of producing the same
CN101342807A
One-step injection molding apparatus and method for preparing sandwich-structured composite materials
CN108638530B
Method for manufacturing lightweight trilayer sandwich structure and lightweight trilayer sandwich structure manufactured thereby
KR101928236B1
Sandwich structure composite material, preparation method and application
CN113954466A